2017
DOI: 10.1007/s12020-017-1332-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism is associated with lower oxytocin concentrations and reduced empathic ability

Abstract: PurposeCentral diabetes insipidus is characterised by arginine vasopressin deficiency. Oxytocin is structurally related to vasopressin and is synthesised in the same hypothalamic nuclei, thus we hypothesised that patients with acquired central diabetes insipidus and anterior hypopituitarism would display an oxytocin deficiency. Moreover, psychological research has demonstrated that oxytocin influences social and emotional behaviours, particularly empathic behaviour. We therefore further hypothesised that centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
0
19
1
1
Order By: Relevance
“…More specifically, we found significant differences in the AQ sub‐scores measuring social skills (AQ‐S) and attention switching (AQ‐AS). The results somewhat contradict the previous findings reported by Daughters et al, 37 who found no difference in AQ scores for patients with hypopituitarism and central diabetes insipidus (CDI) compared to healthy controls. This discrepancy might be a result of differences in AQ measures (we used the 50‐item AQ, Daughters et al 37 applied the 28‐item short version 59 ), as well as differences in patient groups (we included craniopharyngioma patients with a defined hypothalamic damage, Daughters et al 37 included patients with anterior hypopituitarism and an assumed lack of hypothalamic involvement).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…More specifically, we found significant differences in the AQ sub‐scores measuring social skills (AQ‐S) and attention switching (AQ‐AS). The results somewhat contradict the previous findings reported by Daughters et al, 37 who found no difference in AQ scores for patients with hypopituitarism and central diabetes insipidus (CDI) compared to healthy controls. This discrepancy might be a result of differences in AQ measures (we used the 50‐item AQ, Daughters et al 37 applied the 28‐item short version 59 ), as well as differences in patient groups (we included craniopharyngioma patients with a defined hypothalamic damage, Daughters et al 37 included patients with anterior hypopituitarism and an assumed lack of hypothalamic involvement).…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, performance was similar to healthy participants when categorising the age of a viewed face, suggesting the deficit in face recognition to be emotion‐specific. These results are in line with a previous study by Daugthers et al, 37 who also found lower facial emotion recognition scores in patients with hypopituitarism. Interestingly, our data show that emotion recognition was not impaired in all craniopharyngioma patients of our sample.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…No association was observed with measures of empathy. Our own study examined salivary OT concentrations in fifty‐five participants, comprising 20 patients with central diabetes insipidus and anterior hypopituitarism, 15 patients with anterior hypopituitarism alone (clinical controls) and 20 healthy volunteers . Groups were matched for age and gender.…”
Section: Oxytocin In Hypopituitarismmentioning
confidence: 99%